Deteksi Antibodi Terhadap Virus Avian Influenza pada Ayam Buras di Peternakan Rakyat Kota Palangka Raya - Elisa Bernadeta; Iis Yuanita; Lisnawaty Silitonga (Fakultas Peternakan Universitas Kristen Palangka Raya, 2015)
The research was conducted to investigate the antibody titre of native chickens against Avian influenza. The research used Hemaglutination (HA) and Hemaglutination Inhibition (HI) test methods. The result showed that Hemaglutination (HA) and Hemaglutination Inhibition (HI) test methods, could be detect Avian influenza virus in positive AI titre of native chickens.